Spark plug fault recognition using classification method in a spark ignition engine - Azrin, Abdul Aziz; Muhammad Yusri, Ismail (2021)
lnvestigate park plug health based on breakdown voltages signal. Classify spark plug status based on classification method. Evaluate reliabilty of spark plug profile based on WPS.